Optimalisasi Penggunaan QRIS melalui SPPT Elektronik di Bapenda Kota Bandung - Triaji, Ermi; Sumiati, Imas; Vaughan, Regan (Lembaga Pendidikan dan Penelitian Manggala Institute, 2024)
BAPENDA's efforts in increasing public awareness in paying the UN in collaboration with the community through the RW Creative Competition which was attended by a number of regions in the city of Bandung showed positive results. One of them is RW Gempol Sari who won first place in the RW Create competition